2016
DOI: 10.1038/ncomms11869
|View full text |Cite
|
Sign up to set email alerts
|

The necroptosis-inducing kinase RIPK3 dampens adipose tissue inflammation and glucose intolerance

Abstract: Receptor-interacting protein kinase 3 (RIPK3) mediates necroptosis, a form of programmed cell death that promotes inflammation in various pathological conditions, suggesting that it might be a privileged pharmacological target. However, its function in glucose homeostasis and obesity has been unknown. Here we show that RIPK3 is over expressed in the white adipose tissue (WAT) of obese mice fed with a choline-deficient high-fat diet. Genetic inactivation of Ripk3 promotes increased Caspase-8-dependent adipocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
93
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 81 publications
(101 citation statements)
references
References 64 publications
6
93
0
2
Order By: Relevance
“…Most recent, Gautheron et al reported that RIP3 deficiency promotes increased caspase 8‐dependent adipocyte apoptosis and white adipose tissue (WAT) inflammation, associated with impaired insulin signalling in WAT as the basis for glucose intolerance . Their study reported the increased liver injury and apoptosis in RIPK3‐deficient livers, which is similar with our findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most recent, Gautheron et al reported that RIP3 deficiency promotes increased caspase 8‐dependent adipocyte apoptosis and white adipose tissue (WAT) inflammation, associated with impaired insulin signalling in WAT as the basis for glucose intolerance . Their study reported the increased liver injury and apoptosis in RIPK3‐deficient livers, which is similar with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Most recent, Gautheron et al reported that RIP3 deficiency promotes increased caspase 8-dependent adipocyte apoptosis and white adipose tissue (WAT) inflammation, associated with impaired insulin signalling in WAT as the basis for glucose intolerance. 51 Their study reported the increased liver injury and apoptosis in RIPK3- absence of RIP3 exacerbated high fat diet-induced liver injury, associated with increased inflammation and hepatocyte apoptosis. 52 The differences between alcoholic liver disease and nonalcoholic steatohepatitis with RIP3 might be informative in the different colitis models.…”
Section: Discussionmentioning
confidence: 98%
“…RIPK3 and inflammation I Shlomovitz et al deficient diet-induced liver injury, steatosis, inflammation, fibrosis and oxidative stress. 73 In agreement, RIPK3 activation or high expression of RIPK3 was demonstrated in cortical lesions from MS brain specimens; 74 in skin lesions of patients with toxin epidermal necrolysis; 75 in kidney tissues from subtotal nephrectomy-model for chronic kidney injury; 76 in the white adipose tissue of obese mice fed with a choline-deficient high-fat diet and in visceral white adipose tissue of obese humans; 77 and in non-alcoholic fatty liver disease. 78 RIPK3 deficiency also has deleterious outcomes in some models of disease.…”
Section: Figurementioning
confidence: 73%
“…RIPK3 deficiency also has deleterious outcomes in some models of disease. Loss of RIPK3 worsens liver parenchymal cell TAK1 deletion‐induced inflammatory hepatocarcinogenesis, 78 while genetic RIPK3 inactivation promotes increased adipocyte apoptosis, inflammation and impaired insulin signalling 77 …”
Section: Ripk3 In Diseasementioning
confidence: 99%
See 1 more Smart Citation